Phytochemical Investigation of Corchorus olitorius L. Leaves Cultivated in Iraq and it's In Vitro Antiviral Activity - Hayder T. Hasan; Enas J. Kadhim (College of Pharmacy University of Baghdad, 2018)
The aim of our study was to investigate the antiviral activity of the Corchorus olitorius family Tiliaceae cultivated in Iraq against measles virus, and to demonstrate an overview about chemical constituents and pharmacological activity of Corchorus olitorius L. About150 gm Leaves of Corchorus. olitorius were defatted by maceration in hexane for 24 hrs. The defatted plant materials were subjected for extraction after filtration using Soxhlet apparatus, with aqueous methanol 85% as a solvent extraction for 24 hours, the extract was filtered, and the solvent was evaporated under reduced pressure using a rotary evaporator to get a dry extract of about 12 gm. About 4 gm from the residue was suspended in 100ml water, about 3-4ml of 5% sodium hydroxide was added to obtain a basic solution having PH 10 and partitioned with ethyl acetate (3x100ml), the aqueous layer collected and evaporated to dryness. MTT-cell viability assay (3-[4,5-dimethylthiazol-2-yl]-2,5-diphenyl tetrazolium bromide) was conducted on 96-well plates (Falcon), Vero cells were seeded at 1× 104 cells/well to obtain a multiplicity of infection (MOI 10), and at 5 × 103 cells/well to obtain a multiplicity of infection (MOI 5). Different statistical result revealed a significant antiviral activity of the aqueous layer of Corchorus olitorius leaves against measles virus. The preliminary phytochemical tests showed the presence of phenols and flavonoids in the aqueous layer of Corchorus olitorius leaves. The antiviral activity of Corchorus olitorius leaves is mainly due to the phenolics and flavonoids that detected in the aqueous layer.